2019
DOI: 10.3390/su12010288
|View full text |Cite
|
Sign up to set email alerts
|

Abusive Supervision and Organizational Citizenship Behavior: The Mediating Role of Networking Behavior

Abstract: Abusive supervision has been recognized as a serious threat to the health of affected employees and to the sustainable development of organizations. Yet, the mechanism through which abusive supervision affects organizational performance is not well understood. We suggest that abusive supervision restricts important workplace behavior, especially networking behavior and organizational citizenship behavior, which is crucial for building social capital within organizations. We test our hypothesis using a new data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 54 publications
3
18
1
Order By: Relevance
“…This implies that AS needs to be considered as an important agent of service organizations that leads to changes in employees' behaviors and attitudes, which in turn leads to organizations' sustainable development in the market. This important finding is congruent with previous empirical studies [6,7] that suggested that AS is an important factor that affects organizations' sustainable development in service industries. Thus, our study extended our understanding regarding AS and we call for further research on its direct impacts on the sustainable performance of organizations.…”
Section: Theoretical Implicationssupporting
confidence: 91%
See 1 more Smart Citation
“…This implies that AS needs to be considered as an important agent of service organizations that leads to changes in employees' behaviors and attitudes, which in turn leads to organizations' sustainable development in the market. This important finding is congruent with previous empirical studies [6,7] that suggested that AS is an important factor that affects organizations' sustainable development in service industries. Thus, our study extended our understanding regarding AS and we call for further research on its direct impacts on the sustainable performance of organizations.…”
Section: Theoretical Implicationssupporting
confidence: 91%
“…The authors found that abusive supervision has a significant impact on employees' psychological well-being and turnover intention. Kim et al's 2020 study [7] also suggested that abusive supervision is considered a serious threat to the health of the affected employees and the sustainable development of organizations. A close link between organizational leadership/supervision and the sustainable development of organizations was also confirmed by several famous theories and approaches.…”
Section: Introductionmentioning
confidence: 99%
“…In an effective organisation, employees commonly go beyond their formal job responsibilities ('inrole') to perform non-mandatory ('extra-role') tasks with no expectation of additional recognition or CJLG June 2021 27 compensation (Kim et al 2020). Decentralised LGs, like any organisation, will benefit by elevating employees' OCB as a means of promoting better service delivery.…”
Section: Definitions Of Organisational Citizenship Behaviourmentioning
confidence: 99%
“…SCT suggests that individuals' perceptions of CSE and expectations of outcomes vary depending on the situation [54]. Abusive supervision creates a negative organizational atmosphere, threatening personal growth and the sustainable development of the organization [55]. When employees are subjected to abusive supervision, they believe that their supervisors lack respect for them and do not want to be associated with them.…”
Section: Mediating Effect Of Creative Self-efficacymentioning
confidence: 99%